Revitalizing the Mosques Function as a Means of Forming Muslim Scholars and Students in Indonesia - Nur Isnaini, Ummu Kultsum; Nyimasmukti, Billa Ratuwibawa; Rahawarin, Yunus; Asrida, Asrida (Khalifa Journal of Islamic Education, 2019)
This study aims to explore the function extention of the mosque as a means of education for scholars and Muslim students’ formation in Indonesia. This study used qualitative method with descriptive study approach. All data was taken through interview to forty-four informants consisting of students, lecturers and administrators of mosques in two provinces which are Daerah Istimewa Yogyakarta (DIY) and East Java, to strengthen the data, the authors also conducted direct observation to the object of research. Overall results showed that there are six functions of mosques in those two provinces, namely, means of worship, religious education, scientific discussions, entrepreneurship studies, literary studies as well as studies related to art. Referring to the results of this study, which means that the function of the mosque today is no longer just a place of religious worship muslims rituals, but also serves as a means of society development activities in various fields and expertise. According to thee writer this needs to be emulated because in the context of Islam, the mosque should be the center of activity for the Muslims advancement. The concept of the mosque as the central activity of Muslims basically has exemplified by Prophet Muhammad in early Islam development in the medina. The results can also be a reference by other mosque administrators in managing the function of the mosque from being used as a means of worship only.